JSI-124 Suppresses Invasion and Angiogenesis of Glioblastoma Cells In Vitro - Yuan, Guang (Public Library of Science, 2015)

(untitled) (PLoS One)
Glioblastoma multiforme (GBM) is one of the utmost malignant tumors. Excessive angiogenesis and invasiveness are the major reasons for their uncontrolled growth and resistance toward conventional strategies resulting in poor prognosis. In this study, we found that low-dose JSI-124 reduced invasiveness and tumorigenicity of GBM cells. JSI-124 effectively inhibited VEGF expression in GBM cells. In a coculture study, JSI-124 completely prevented U87MG cell–mediated capillary formation of HUVECs and the migration of HUVECs when cultured alone or cocultured with U87MG cells. Furthermore, JSI-124 inhibited VEGF-induced cell proliferation, motility, invasion and the formation of capillary-like structures in HUVECs in a dose-dependent manner. JSI-124 suppressed VEGF-induced p-VEGFR2 activity through STAT3 signaling cascade in HUVECs. Immunohistochemistry analysis showed that the expression of CD34, Ki67, p-STAT3 and p-VEGFR2 protein in xenografts was remarkably decreased. Taken together, our findings provide the first evidence that JSI-124 effectively inhibits tumor angiogenesis and invasion, which might be a viable drug in anti-angiogenesis and anti-invasion therapies.